Peningkatan Kesiapan Persalinan Aman pada Ibu Hamil Rawan Bencana - Kholifatul Ummah; Theresia Detiati Ngongo; Nisfu Laila (Health Care : Journal of Community Service, 2026)
This community service program aimed to improve safe childbirth preparedness among pregnant women in a disaster-prone area, particularly in Nogosari Village, Pacet District, Pasuruan Regency, East Java. The partner problems included limited birth and complication readiness planning, restricted access to health services during disasters, insufficient knowledge among mothers and families regarding danger signs, and the lack of an optimized community-based pregnant women alert system. The methods consisted of identifying and registering pregnant women, classifying pregnancy risks, providing education and counseling on birth preparedness and complication readiness, establishing an RT/RW-level pregnant women alert system, conducting childbirth preparedness simulations, and evaluating family readiness. The results showed improved knowledge among pregnant women and families regarding pregnancy danger signs, the development of plans for birth location and emergency transportation, preparation of childbirth readiness bags, and the establishment of simple coordination among the village midwife, cadres, and families. This program is important to strengthen family and community preparedness in supporting safe childbirth in disaster-prone areas.